2022
DOI: 10.24130/eccdjecs.1967202262309
|View full text |Cite
|
Sign up to set email alerts
|

Okul öncesi öğretmenlerinin ödül ve ceza uygulamalarına yönelik görüşleri

Abstract: Bu araştırmanın amacı, okul öncesi öğretmenlerinin eğitim-öğretim sürecinde kullandıkları ödül ve ceza uygulamalarına yönelik görüşlerini incelemektir. Özellikle okul öncesi yaş; çocukların bilişsel, kişisel, duyuşsal, sosyal ve ahlaki gelişimleri bakımından oldukça kritik bir önem taşıdığından, bu yaştaki çocukların eğitiminde kullanılan ödül ve ceza uygulamalarının doğru kullanılması bir gereklilik haline gelmiştir. Bu araştırma nitel yöntemle desenlenmiş fenomonolojik bir çalışmadır. Araştırmada yarı yapıla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Only one study focuses on measuring parental reward behaviors (Atli et al, 2022). There are robust studies related to the use of rewards and praise in educational processes, but most of them are qualitative research involving interviews with teachers (Cumhur, Kartal, Karademir & Erdinç, 2019;Güzelyurt et al, 2019;Han and Altunhan, 2022;Ġlgar & Örs, 2021) or review articles (Gündüz & Balyer, 2011;Köçer & Çınar, 2021). These studies contribute to the field by proposing strong alternatives to rewards.…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one study focuses on measuring parental reward behaviors (Atli et al, 2022). There are robust studies related to the use of rewards and praise in educational processes, but most of them are qualitative research involving interviews with teachers (Cumhur, Kartal, Karademir & Erdinç, 2019;Güzelyurt et al, 2019;Han and Altunhan, 2022;Ġlgar & Örs, 2021) or review articles (Gündüz & Balyer, 2011;Köçer & Çınar, 2021). These studies contribute to the field by proposing strong alternatives to rewards.…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 99%
“…According to the internal control-focused approach, rewards may be effective, but their impact is often short-lived, and sometimes they have no effect at all (Han & Altunhan, 2022;Yaman & Güven, 2014). Various meta-analysis studies have shown that internal control-focused, social, and emotional learning development programs help reduce student problems, enhance social skills, and improve academic achievement (Taylor, Oberle, Durlak & Weissberg, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…One of the main problems of STEM education, which is one of the methods of interdisciplinary learning in all of the processes starting from preschool education -the first stage of education -up to higher education, is the integration of the teaching program (Uğraş, 2017). Unfortunately, it has been known that STEM education is not grasped very well by educators, and even those who see it of vital importance, fail to demonstrate a clear vision of it (Brown et al, 2011).…”
Section: S T Emmentioning
confidence: 99%
“…Another notable study focusing on the preschool level was conducted by Han and Altunhan (2022), shedding light on the utilization of reward and punishment. Han and Altunhan (2022) discovered that preschool teachers often employ symbolic and social rewards rather than material incentives. These rewards are utilized to motivate students, modify behavior, and establish classroom rules.…”
Section: Introductionmentioning
confidence: 99%